REPRESENTASI IDENTITAS ETNIS MELALUI BAHASA DALAM FILM SERI “ARAB MAKLUM” - Syaifullah, Syaifullah; Adila, Wildi; Setyawan, Cahya Edi (Widyaparwa, 2024)
This study describes the role of language in presenting culture and ethnic identity through the medium of the film series "Arab Maklum". This film presents the story of an Arab family who persistently maintains their ancestral traditions in the modern era. The main data source of this study is the transcription of the film's dialogue, which is analyzed using content analysis techniques. Sapir-Whorf's theory is used as a conceptual framework to understand the influence of language on ethnic identity. The results of the study show that the film series "Arab Maklum" uses Arabic effectively to present Arab ethnic identity. The use of Arabic phrases and terms in everyday conversations, social events and family interactions shows a strong attachment to their cultural heritage and ethnic identity. Arabic does not only function as a means of communication, but also as a marker of deep ethnic identity, which is strengthened through dialogues that reflect Arab cultural values and traditions. This study not only enriches academic understanding of the relationship between language, culture and ethnic identity, but also highlights the importance of in-depth analysis in media and cultural studies. These findings provide important insights for filmmakers and media researchers to create more sensitive and accurate works in cultural and ethnic representation, as well as strengthening the literature on the influence of language in media.Penelitian ini memaparkan peran bahasa dalam mempresentasikan budaya dan identitas etnik melalui medium film seri “Arab Maklum”. Film ini menampilkan kisah keluarga Arab yang gigih mempertahankan tradisi leluhurnya pada era modern. Sumber data utama penelitian ini adalah transkripsi dialog film, yang dianalisis menggunakan teknik analisis konten. Teori Sapir-Whorf digunakan sebagai kerangka konseptual untuk memahami pengaruh bahasa terhadap identitas etnik. Hasil penelitian menunjukkan bahwa film seri "Arab Maklum" menggunakan bahasa Arab secara efektif untuk mempresentasikan identitas etnis Arab. Penggunaan frasa dan istilah Arab dalam percakapan sehari-hari, acara sosial dan interaksi keluarga menunjukkan keterikatan yang kuat dengan warisan budaya dan identitas etnis mereka. Bahasa Arab tidak hanya berfungsi sebagai alat komunikasi, tetapi juga sebagai penanda identitas etnis yang mendalam, yang diperkuat melalui dialog-dialog yang mencerminkan nilai-nilai dan tradisi budaya Arab. Penelitian ini tidak hanya memperkaya pemahaman akademis tentang keterkaitan antara bahasa, budaya, dan identitas etnis, tetapi juga menyoroti pentingnya analisis mendalam dalam studi media dan budaya. Temuan ini memberikan wawasan penting bagi pembuat film dan peneliti media untuk menciptakan karya yang lebih sensitif dan akurat dalam representasi budaya dan etnis, serta memperkuat literatur tentang pengaruh bahasa dalam media.